2013
DOI: 10.5539/hes.v3n5p11
|View full text |Cite
|
Sign up to set email alerts
|

Confronting the Need for Conceptual Change in Pre-Service Science Education

Abstract: During a five-year period the authors taught over 100 students in a graduate course (The Nature of Science) counting toward teacher certification at the Harvard Graduate School of Education. Despite the fact that students had undergraduate degrees in the sciences, most of them found the application of models in science challenging and the epistemological consequences unsettling. Moreover, students found it especially difficult to use a model to correctly generate predictions, which was starkly illustrated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…A conceptual change model of learning in teacher education has been proposed as an important methodology for research on how teachers learn (Schwartz, Shapiro and Gregory 2013), but more research utilizing this method is warranted. Conceptual change has, however, been used as an analytic tool in research on teachers' learning about diversity (Larkin 2012) and inquiring into 'cultural values' as a non-conceptual factor (Abd-El-Khalick and Akerson 2004).…”
Section: Why Conceptual Change?mentioning
confidence: 99%
“…A conceptual change model of learning in teacher education has been proposed as an important methodology for research on how teachers learn (Schwartz, Shapiro and Gregory 2013), but more research utilizing this method is warranted. Conceptual change has, however, been used as an analytic tool in research on teachers' learning about diversity (Larkin 2012) and inquiring into 'cultural values' as a non-conceptual factor (Abd-El-Khalick and Akerson 2004).…”
Section: Why Conceptual Change?mentioning
confidence: 99%
“…Several studies, including Stepans and McCormack (1985), Skamp (1989), and Appleton (1995) found that more formal science training was not associated with increased levels of conceptual science knowledge. In more recent work, Schwartz, Shapiro, and Gregory (2013) found that nearly all of the students in their graduate level teacher certification course did not understand the basic structures of science, despite all of them being science majors. The study confronted teacher candidates with a situation in which they had to apply a theoretical model (Archimedes' principle) to explain their observations and make predictions.…”
Section: Nature Of Knowledge Needed For Teaching Physical Sciencementioning
confidence: 99%